Ultra-thin C3N4 nanosheets for rapid charge transfer in the core–shell heterojunction of α-sulfur@C3N4 for superior metal-free photocatalysis under visible light1. Issue 20 (6th March 2015) - Dang, Xueming; Zhang, Xiufang; Zhang, Weiqiang; Dong, Xiaoli; Wang, Guowen; Ma, Chun; Zhang, Xinxin; Ma, Hongchao; Xue, Mang
<x xml:space="preserve">Abstract</x> Enhanced visible-light-driven photocatalytic ability is obtained by fabricating an α-S@C3N4 heterojunction with ultra-thin C3N4 nanosheet as the means of rapid charge transfer.